Intravenous Urography in Cats - Comparison of Bolus, Abdominal Compression and Infusion Techniques - Akyol, Eyüp Tolga; Arican, Mustafa (Acta Scientiae Veterinariae, 2023)
Background: Diagnostic imaging is an integral part of the examination of patients with urinary tract pathologies and many imaging modalities are available. Owing to easy accessibility and low cost, radiography used together with ultrasonography as one of the first-step imaging methods in order to visualize the urinary system. Contrast-enhanced radiographic examination of the upper urinary system “intravenous urography” (IVU) can be performed with bolus injection, abdominal compression (with bolus injection) and infusion techniques. The aim of present study was to evaluate the urograms obtained in cats with urinary system complaints, compare the application of the IVU techniques and urogram quality, and interpret their diagnostic efficacy. Materials, Methods & Results: A total of 30 cats (of different age, breed, sex and weight) with urinary system complaint brought to Selcuk University Veterinary Faculty and Balikesir University Veterinary Faculty Surgery Clinics were included in the study. The cats were randomly divided into 3 groups with 10 cats in each group. In these groups, IVU was performed with bolus (Group 1), infusion (Group 2) and abdominal compression with bolus injection (Group 3) techniques. Non-ionic monomeric contrast agent iohexol3 (300 mg I/mL, GE Healthcare) at a dose of 800 mg I/kg was administered as an IV bolus injection in the Bolus group; iohexol at a dose of 1200 mg I/kg was diluted in an equal volume of 0.9% NaCl solution and the prepared solution was administered as an IV infusion through the catheter within 10 min in the Infusion group; iohexol at a dose of 800 mg I/kg was administered through the catheter after an elastic compression band was placed around the caudal abdomen to provide compression on the ureters in the bolus injection with abdominal compression group. The contrast agent (iohexol) injection was well tolerated by all cats. None of the cats developed anaphylactoid reactions or anesthesia-related complication. Changes observed in the heart and respiration rates and body temperature during the procedure did not show a statistically significant difference between the groups (P > 0.05). The renal and ureteral opacity scores and groups were compared, there was a significant difference was observed (P < 0.05). Urograms with “1 point” and “2 points” in kidney opacity scores were in the bolus injection group; urograms with “3 points” and “4 points” showed a statistically significant increase in the infusion and abdominal compression groups (P < 0.05). Urograms with “2 points” and “3 points” in ureteral opacity scores did not show a statistically significant difference (P > 0.05). Discussion: Currently, radiological IVU can still be used as a feasible, economical and valuable diagnostic tool with appropriate techniques, contrast agents and dose selection. For this purpose, patient preparation before IVU is very important to increase the interpretation ability of the urograms obtained. Sedation or anesthesia is not required to obtain better urograms. The bolus injection technique would be preferable for evaluating the anatomical position of the kidneys and observing the renal parenchyma. Urograms up to 20 min after the injection in the ventrodorsal (VD) position would be sufficient for proper observation of the nephrography phase. The infusion technique would be preferable for evaluating the collecting system. Urograms up to 20 min following the completion of the infusion in the VD position would be sufficient for proper observation of the pyelography phase and ureters. Urograms should be obtained in the VD and lateral positions for ureteral evaluation. Urograms taken after 5 or 40 min would be sufficient, depending on the ureteral part to be examined. Keywords: abdominal compression, bolus, cat, infusion, urography.